Metode Injeksi pada Teknik Menari Sanggar Tari Swardance Pandanwangi Kabupaten Malang - Divva Marchanda Adiha Sholichin; Wida Rahayuningtyas (Gesture: Jurnal Seni Tari, 2026)
This study presents the creative practice of Eko Ujang in the invention of the Sekar Kadipaten Dance and is intended to find out how the creative process of innovating it from the Wayang Topeng Malangan dance adaptation. The effort is motivated by the development of Malangan creative traditional dance which is based on the Wayang Topeng Malangan art. The main framework reference in this paper is the creative process and results expected. The research method that will be used is a descriptive qualitative method with an ethnochoreology approach. The data collection process uses a semi-structured interview method and combines literature studies. The results of this study describe the creative process of inventing the Sekar Kadipaten Dance which was originated from the process of adaptation and development of dancing work patterns referring to Malangan traditional dance. This research can be used as a critical reflection on the innovation of creative dance works based on Malangan traditional art. This can add to the reference about creative dance art formation that has developed in Malang Regency.